Pencapaian Zakat Terhadap Sustainability Development Goals (SDGs) Di Tiga Desa Di Kabupaten Majalengka: Implementasi Indeks BI-WAS - gustani, gustani; Yulinar, Marina (JURNAL EKONOMI SYARIAH, 2021)
Zakat as worship with a social dimension has the same goals as the Sustainable Development Goals (SDGs) program. This study aims to measure the state of clean water sources along with the current state of sanitation conditions in three villages in Majalengka Regency. The results of this study are expected to be a reference for zakat distribution programs. The method used is a mixed method approach, which is a combination of qualitative and quantitative. The measurement indicators use the Index for Sustainable Clean and Safe Water and Santation, or the BAZNAS Index for the Sustainability of Clean Water and Sanitation (BI-WAS) developed by the BAZNAS Puskas. The results of this study show that the BI-WAS value in the three villages is above 60%, which means that public awareness of clean water and sanitation is good so that the existence of zakat programs related to this is less needed.Â Keywords: Zakat; SDGs; BI-WAS